Diverse Applications of the Anti-Diabetic Drug Metformin in Treating Human Disease - Chris-Tiann Roberts; Nicole Raabe; Lara Wiegand; Ashraf Kadar Shahib; Mojgan Rastegar (Pharmaceuticals)
Metformin is a commonly used drug for treating type 2 diabetes. Metformin is an inexpensive drug with low/no side effects and is well tolerated in human patients of different ages. Recent therapeutic strategies for human disease have considered the benefits of drug repurposing. This includes the use of the anti-diabetic drug metformin. Accordingly, the anti-inflammatory, anti-cancer, anti-viral, neuroprotective, and cardioprotective potentials of metformin have deemed it a suitable candidate for treating a plethora of human diseases. As results from preclinical studies using cellular and animal model systems appear promising, clinical trials with metformin in the context of non-diabetes-related illnesses have been started. Here, we aim to provide a comprehensive overview of the therapeutic potential of metformin in different animal models of human disease and its suggested relationship to epigenetics and ailments with epigenetic components.